Meta‐analysis and critical review of trophic discrimination factors ( Δ 13 C and Δ 15 N ): Importance of tissue, trophic level and diet source - Stephens, Ryan B.; Shipley, Oliver N.; Moll, Remington J. (Functional ecology, 2023)
Robustly quantifying dietary resource use and trophic position using stable isotopes requires accurate trophic discrimination factors (TDF; Δ 13 C and Δ 15 N for carbon and nitrogen, respectively), defined as the isotopic difference between consumer and diet. Early TDF studies converged on values of around 1.0‰ for Δ 13 C and 3.4‰ for Δ 15 N but more recent work indicates that TDF values may be more nuanced, depending on taxa, tissues, trophic level and diets. Yet, the relative importance of these factors remains unclear. Focusing on vertebrates (birds, fish, herptiles and mammals), we conducted a literature review of 279 studies that estimated TDF values and used a Bayesian framework to determine how tissue type, trophic level and diet source influence variation in Δ 13 C and Δ 15 N. Additionally, we reviewed 358 trophic ecology studies to determine if studies accounted for these factors during their TDF selection process. For Δ 13 C, vertebrates showed consistent patterns among tissue types (likely influenced by amino acid composition) and between trophic levels and diet sources (likely a result of dietary protein content and metabolic routing). Comparatively, for Δ 15 N, vertebrates showed considerable variation among tissue types and trophic levels, likely due to differences in tissue synthesis and physiological capabilities. Overall, Δ 13 C ranged from −5.1‰ to 9.1‰ and Δ 15 N from −3.3‰ to 9.7‰, underscoring that 1.0‰ for Δ 13 C and 3.4‰ for Δ 15 N are not universally appropriate. Moreover, both Δ 13 C and Δ 15 N varied by more than 9‰ within a single species and tissue type, demonstrating that using TDF values from the same, or similar, species may not be appropriate if diet and trophic level are not considered. Despite the importance of diet source on TDF values, most trophic ecology studies did not account for it. Further, most fish studies relied on literature review values that failed to account for tissue type, trophic level and diet source. To aid ecologists in diet and trophic assessments of vertebrates, we used our meta‐analysis to model taxon‐specific TDF estimates (mean ± SD) for each tissue type, trophic level and diet source combination. These more refined TDF values should improve ecological assessments that use stable isotopes. Read the free Plain Language Summary for this article on the Journal blog.